(untitled) (Revista de Ciências Agroveterinárias, 2019)
This work aimed to determine weed interference on common bean crop productivity (Phaseolus vulgaris). The experiment was carried out in the agricultural crop-year of 2016/2017 in the county of Curitibanos, SC. The experimental design was a randomized block design with twelve treatments and five replications. The treatments were arranged in a factorial scheme 2 x 6. The first factor was represented by two interference models being a period of coexistence or period before interference (PAI), and another control period or total period of interference prevention (PTPI). The second factor consisted of 6 growing seasons in which the crop cohabited or was kept free of the presence of weeds (0, 7, 15, 30, 60, 102 days after emergence - DAE). The following parameters were evaluated: the plant stand count at 2.0 meters, number of pods per plant, the mass of a hundred grains, and the final yield. Our results demonstrated that the critical period of interference prevention (PCPI) was situated between 5 and 54 DAE. Weed interference during the whole cycle of the bean crop reduced the number of plants, the number of pods per plant, and the yield of the cv. IPR Tangará, being the last variable in 80.4%.